Carbono en necromasa y suelo en parcelas I, II, III, IV del arboretum “El Huayo”, Puerto Almendra, Loreto – Perú, 2021 - Pezo Cauper, Jean Paul (2023)
The present research work determined the necromass and its carbon, in addition, the carbon stored in the soil at different depths of plots I, II, III, IV of the Arboretum "El huayo" of CIEFOR-Puerto Almendra. The methodology applied was to obtain 5 amples of necromass of 1 m2 per plot in total 20 m2 and 3 pits of 70 cm * 70 cm * 30 cm were made for each plot and at depths between 00 cm-10 cm, 10 cm - 20 cm and 20 cm - 30 cm adding a total of 12 test pits and 36 soil samples, to then condition it and determine the organic matter by the calcination method and applying mathematical formulas, calculate the organic carbon by depth level and by plot, taking the accumulation of necromass carbon and soil carbon in t/ha. The results show the highest accumulation of necromass and carbon is found in plot 1 with 9,37 t/ha and 4,69 t/ha respectively, followed by plots 2, 4 and 3. The highest accumulation of carbon storage on the ground it is in plot 4 with 74,15 t/ha followed by plot 2 and plot 3 with 57,28 t/ha and 51,59 t/ha, plot 1 being less accumulated with 39,54 t /ha. The carbon in soils between 00 cm - 10 cm deep was obtained the highest accumulation with 59,90 t/ha followed by 10 cm - 20 cm with 54,55 t/ha and the lowest between 20 cm - 30 cm with 52,48 t/ha. The analysis of variance between soil carbon and necromass carbon using the Kruskal-Wallis test (p)= 0, shows that it is highly significant at (p)=0.05, therefore, the proposed hypothesis is accepted.